Essential Alternatives to Contemporary Missionary Training: For the Sake of Vulnerability to the Majority World (Africa). (October 2019) - Harries, Jim
When the only advice on offer is unhelpful, a potential missionary might need to be advised to seek an alternative. Jesus, we take it, was not building a worldly empire (John 18:36). Christian mission has become associated with colonialism. Dominant advice often pushes Western missionaries to positions of strength. In order to be vulnerable, one needs an alternative to such advice. Economic domination of Africa by the West makes it hard to know when Africa's people, long engrossed in patron/client relationships, are not talking for power. Use of English to describe Africa leads to massive false imputing of Western histories onto African societies. A little linguistic wisdom exposes the naivety of many contemporary understandings of the acumen of translation.